Rabindranath Tagore and Feminism - Singha, Y Monojit (International Journal of Psychosocial Rehabilitation, 2020)
Rabindranath Tagore, through his body of work, introduced the idea of feminism in India. His female protagonists talked about individuality, liberty, freedom, justice, power, dignity and rights. Often they would challenge patriarchy and talk about practices which are considered taboo even today. Feminism in Rabindranath Tagore challenges the traditional view of woman as the weaker sex. This is the challenge which is undertaken by most of the supporter of feminism. Thus the paper analyses the philosophical spirit of Tagore as an advocate of feminist in his dramatic and poetic writings.